2016
DOI: 10.1039/c5cc08895j
|View full text |Cite
|
Sign up to set email alerts
|

A new cascade halosulfonylation of 1,7-enynes toward 3,4-dihydroquinolin-2(1H)-ones via sulfonyl radical-triggered addition/6-exo-dig cyclization

Abstract: A new cascade three-component halosulfonylation of 1,7-enynes for efficient synthesis of densely functionalized 3,4-dihydroquinolin-2(1H)-ones has been established from readily accessible arylsulfonyl hydrazides and NIS (or NBS). The reaction pathway involves in situ-generated sulfonyl radical-triggered α,β-conjugated addition/6-exo-dig cyclization/radical coupling sequence, resulting in continuous multiple bond-forming events including C–S, C-C and C-I (or C-Br) bonds to rapidly build up molecular complexity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
33
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 123 publications
(34 citation statements)
references
References 51 publications
0
33
1
Order By: Relevance
“…Annulation/1,7-bifunctionalization reactionso f1,6-enynes. tion, [69] and halosulfonylation [70] of 1,7-enynes to afford av ariety of polyfunctionalized 3,4-dihydroquinolin-2(1H)-ones 170-172,r espectively (Scheme 42). Following these successful works, Li, Guo, and co-workers recently reported as elenosulfonation of N-tethered 1,7-enynes with sulfinic acids and diphenyl diselenide for the formation of multifunctional 3,4-dihydroquinolin-2(1H)-ones 173 in good-to-excellent yields under both batch andf low conditions (Scheme 43).…”
Section: Radical-triggered Annulation/1n-bifunctionalization Reactionsmentioning
confidence: 99%
“…Annulation/1,7-bifunctionalization reactionso f1,6-enynes. tion, [69] and halosulfonylation [70] of 1,7-enynes to afford av ariety of polyfunctionalized 3,4-dihydroquinolin-2(1H)-ones 170-172,r espectively (Scheme 42). Following these successful works, Li, Guo, and co-workers recently reported as elenosulfonation of N-tethered 1,7-enynes with sulfinic acids and diphenyl diselenide for the formation of multifunctional 3,4-dihydroquinolin-2(1H)-ones 173 in good-to-excellent yields under both batch andf low conditions (Scheme 43).…”
Section: Radical-triggered Annulation/1n-bifunctionalization Reactionsmentioning
confidence: 99%
“…BHT as a radical inhibitor was used to detect the above transformation and the desired product 4 a was obtained in 45% yield (Scheme 3a). [8] These results suggested that this reaction may not include a radical mechanism and TBHP could oxidize the iodine anion to molecular iodine. Without triethylamine, the reaction of 1 p with 2 a was carried out under standard conditions, the product 4 p was isolated in 30% yield along with 28% yield of iodinated product 5 p, determined by X-ray diffraction analysis (Scheme 3b and see Supporting Information), [10] indicating that iodinated product may be an intermediate for forming final product 4.…”
mentioning
confidence: 99%
“…A survey of literatures revealed that the generation of sulfonyl radicals from sulfonyl hydrazides under oxidative conditions is well established. [8] For these reasons, the reaction of yne-allenones with sulfonyl hydrazides was conducted by combining I 2 and tert-butyl hydroperoxide (TBHP) as a catalytic oxidative system. Instead of the expected cyclobuta[a] naphthalen-4-ol products 3 (Scheme 1c), the reaction proceeded in another direction to give 3,4-dihydrobenzo[f]phthalazin-6-ols 4, accompanied with naphthalen-1-ol intermediates 5.…”
mentioning
confidence: 99%
“…Specifically, readily available sulfonyl hydrazides have become general sulfonyl radical sources to install sulfonyl functional group. [5][6][7][8][9] In this context, sulfonyl hydrazides have been widely investigated as radical precursors for coupling with alkenes, [5] alkynes, [6] indoles, [7] 1,n-enynes [8] and others. [9] Recently, several groups have focused on developing sulfonyl radical-enabled cyclization of 1,n-enynes.…”
mentioning
confidence: 99%